Calorimetric Behaviour of Electric Cables - Katarzyna Kaczorek-Chrobak; Jadwiga Fangrat; Bartłomiej K. Papis (Energies, 2021)
A routine cone calorimeter procedure, the theoretical analysis method, based on a set of ignitability data from the cone calorimeter, has been performed. The five sets of ignition times at different irradiance levels were used for obtaining experimental data needed for analysis. The cone calorimeter tests were performed with horizontal specimens of the size 100 mm × 100 mm consisting of eight pieces of commercial poly(vinyl chloride) coaxial power cable. Specimen combustion was carried out under external heat flux of constant values equal to 10, 20, 30, 40 and 50 kW·m−2, respectively. Standard fire parameters and time to ignition were used for analysis. The results indicate that for each fire parameter, a rising trend with an increase in radiant heat flux has been observed. It was shown that the use of poly(vinyl chloride)-based cables is a potential fire safety hazard due to the emission of heat and a large amount of acid smoke. Quintiere’s theory has been shown as a useful tool for fire modelling by using the data from small-scale tests rather than large geometrical scale cable experiments. Large scale cable test (EN 50399) results are also presented and compared with cone calorimeter data.